Chemical Composition and Enantiomeric Distribution of Volatile Components of Vitex trifolia Essential Oil - Mudianta, I Wayan; Apriani, Ni Putu; Dewi, Indah Kusuma; Ayuni, Ni Putu Sri (The Journal of Pure and Applied Chemistry Research, 2025)
This study addressed the need to fully characterized the chemical composition of Vitex trifolia essential oil by using both capillary non-chiral and chiral GC-MS column. Employing the same oven program, the essential oil was injected into a capillary non-chiral column (RTX5-MS) and a derivatized cyclodextrin based chiral column (Rt-βDEXse). Five major terpenes were identified from both columns including α-pinene, sabinene, eucalyptol, α-terpinyl acetate, and β-caryophyllene. Seventeen volatile components were identified from each column that can be grouped into monoterpenes, sesquiterpenes, and their oxygenated derivatives. The enantio-resolution of the oil indicated the presence of two pairs of enantiomers including (+)- and (˗)-sabinene (5.59% and 94.41%) as well as (˗)- and (+)-α-terpineol (22.35% and 77.65%). The full chromatographic characterization of the essential oil can serve as chemotaxonomic assignments for detecting adulteration and for indicating of genuineness.